PENGARUH KINERJA KEUANGAN & PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (NILAI PASAR) - Moh Syadeli (Politeknik Negeri Malang, 2017)
This study discusses the influence of financial performance and disclosure of Corporate Social Responsibility to company value on food and beverages company that exist in BEI in period 2011-2015. Population used in this research is food and beverages company that exist in BEI. The number of registered companies amounted to 19 companies with the collection of samples using purposive sampling method that ultimately filter the sample of 7 companies with a period of 5 years The results of the research found that the F test conducted proves that ROA, ROE and CSR disclosure affect together to the value of the company. T test conducted to determine the relationship of each independent variable to the dependent variable shows that ROA and CSR disclosure does not have a significant effect on corporate value while ROE has a significant influence on corporate value. The researchers also tested the coefficient of determination which results showed that the independent variables in this study (ROA, ROE, and CSR Disclosure) in this study amounted to 43.4% and 56.6% were the effects of other variables not used in the study this.